Procurement Process Optimization and Firm Supply Chain Performance: The Mediating Effect of Information Technology Integration - Issah, Ofori; Yeboah, Hanson Obiri; Agboyi, Rosemary Makafui; Baah, Samuel Agyei; Ofori, Agyeman (International Journal of Economic Policy, 2025)
Purpose: The main objective of the study was to assess the mediating effect of information technology integration on the relationship between procurement process optimization and firm supply chain performance. Methodology: The study adopts a quantitative explanatory research design. This design is suitable as it examines the causal relationships between procurement process optimization, information technology integration, and firm supply chain performance. A purposive sampling technique was used to obtain a sample size of 200. The findings of the study indicate a positive and significant direct effect of Procurement Process Optimization on Firm Supply Chain Performance. The findings of the study also demonstrate a strong positive direct effect of Procurement Process Optimization on Information Technology Integration. Findings: The findings of the study indicate a substantial positive impact of Information Technology Integration on Firm Supply Chain Performance. The findings of the study finally show the indirect effect of Procurement Process Optimization on Firm Supply Chain Performance mediated by Information Technology Integration. Unique Contribution to Theory, Policy and Practice: This study advances theory by integrating procurement optimization, IT integration, and supply chain performance, informs policy by advocating for digital procurement reforms, and provides practical insights for firms to enhance supply chain efficiency through technology-driven procurement strategies. The study offers insights into how optimizing procurement processes through IT integration can reduce corruption, inefficiencies, and delays in public procurement systems. The research further provides a roadmap for businesses to integrate procurement processes with supply chain management for greater agility and competitiveness.